Incidental diagnosis of pulmonary cryptococcosis by rebiopsy for epidermal growth factor receptor T790M mutation: A case report - Hiroshi Kobe; Shinya Yokoe; Tadashi Ishida (Thoracic Cancer, 2023)
Abstract Cryptococcosis is an invasive fungal infection that can occur in cancer patients. A case of pulmonary cryptococcosis in a patient treated with erlotinib + ramucirumab for epidermal growth factor receptor (EGFR) L858R point mutation‐positive non‐small cell lung cancer is presented. During chemotherapy, a new pulmonary nodule was found and considered progressive disease. Examination of the biopsy specimen taken to identify EGFR T790M mutation incidentally led to the diagnosis of pulmonary cryptococcosis. Three months after taking fluconazole, chest computed tomography showed that the pulmonary nodule had shrunk. New pulmonary nodules during lung cancer treatment require careful attention, not only because of disease progression, but also because of the possibility of infection in an immunocompromised host.